2004
DOI: 10.1071/rdv16n1ab12
|View full text |Cite
|
Sign up to set email alerts
|

12prediction of Bull Fertility by Computer Assisted Semen Analysis

Abstract: We developed a method to evaluate bovine sperm membranes in normal (1G) and simulated microgravity (Sim-µG). Bovine spermatozoa are used as a model system because they have cellular membranes analogous to those of other cell types, and yet are much simpler because they have no cytoplasm and do not participate in DNA transcription or mRNA translation. They can be cultured as single cells and are easily evaluated for membrane characteristics using flow cytometry. These features make the mammalian spermatozoon a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…In cattle, several sperm velocity parameters have been shown to be positively associated with fertility rates (Cseh et al 2004, Gillan et al 2008. In the present research, FSF spermatozoa frozen with the DF method displayed higher velocities (VAP, VSL, VCL) at the majority of time points during the 24-h post-thaw incubation than Control spermatozoa frozen with the straw or DF method.…”
Section: Discussionsupporting
confidence: 51%
“…In cattle, several sperm velocity parameters have been shown to be positively associated with fertility rates (Cseh et al 2004, Gillan et al 2008. In the present research, FSF spermatozoa frozen with the DF method displayed higher velocities (VAP, VSL, VCL) at the majority of time points during the 24-h post-thaw incubation than Control spermatozoa frozen with the straw or DF method.…”
Section: Discussionsupporting
confidence: 51%
“…However, there is controversy about which particular sperm kinematic could best predict bull fertility (Pepper‐Yowell 2011, Simonik and others 2015). Cseh and others (2004) found that velocity parameters such as VAP, VCL and VSL from frozen‐thawed bull sperm samples had high correlations with non‐return rates (fertility rates), VAP being the one with highest correlation, whereas Nagy and others (2015) reported that VAP values could be a potential predictor of bull fertility. However, Gillan and others (2008) demonstrated that only VSL in post‐thaw samples was correlated with fertility rates.…”
Section: Discussionmentioning
confidence: 99%
“…In modern years, science progressed rapidly mainly in computer and video processing; therefore, the functionality and accuracy of CASA system's latest versions are dramatically enhanced and provide more knowledge on the different sperm movement characteristics. Due to the sperm motility 's key role in the reproductive cycle, theses systems have capability to allow us to enter a new diagnostic andrological age and predict the semen's ability to fertilize [6].…”
Section: Introductionmentioning
confidence: 99%